A microsatellite genetic linkage map for zebrafish (Danio rerio) - Knapik, E W; Goodman, A; Ekker, M; Chevrette, M; Delgado, J; Neuhauss, S; Shimoda, N; Driever, W; Fishman, M C; Jacob, H J (Nature genetics, 1998)
We have constructed a zebrafish genetic linkage map consisting of 705 simple sequence-length polymorphism markers (SSLPs). The map covers 2350 centimorgans (cM) of the zebrafish genome with an average resolution of 3.3 cM. It is a complete map in genetic mapping terms (there is one linkage group for each of the 25 chromosomes), and it has been confirmed by somatic-cell hybrids and centromere-mapping using half-tetrad analysis. The markers are highly polymorphic in the zebrafish strains used for genetic crosses and provide a means to compare genetic segregation of developmental mutations between laboratories. These markers will provide an initial infrastructure for the positional cloning of the nearly 600 zebrafish genes identified as crucial to vertebrate development,and will become the anchor for the physical map of the zebrafish genome.